Premi Asuransi Jiwa Joint Life dan Last Survivor dengan Asumsi Balducci - Hasriati, Hasriati; Rikawati, Putri (Talenta Conference Series: Science and Technology (ST), 2019)
Makalah ini membahas premi asuransi jiwa joint life dan last survivor dwiguna dengan peluang hidup menggunakan asumsi Balducci. Dalam hal ini peserta asuransi dibatasi hanya untuk dua orang yang berusia x dan y tahun dengan nilai tunai anuitas hidup awal yang menggunakan peluang hidup asumsi Balducci. Dalam asuransi jiwa last survivor perhitungan preminya berkaitan dengan asuransi jiwa perorangan dan asuransi jiwa joint life. Premi tahunan asuransi jiwa last survivor diperoleh dengan menentukan nilai tunai anuitas hidup dan premi tunggalnya. This article discusses the premium of endowment of life insurance of joint life and the last survivor status with life appourtunity using Balducci assumptions. In this article, insurance clients are limited to only two persons who are x and y years old with the premium paid until the last death of the insurance clients. In life insurance of the last survivor the premium is determined by associated with individual life insurance and life insurance joint life. The annual premium of life insurance of the last survivor is obtained by determining the present value of annuity and single premium.